Influence of pore structure and impregnation–drying conditions on the solid distribution in porous support materials. Issue 16 (9th December 2016) - Börnhorst, M.; Walzel, P.; Rahimi, A.; Kharaghani, A.; Tsotsas, E.; Nestle, N.; Besser, A.; Kleine Jäger, F.; Metzger, T.
ABSTRACT: Deposition of solids within porous materials from a drying solution is an important phenomenon in numerous natural and industrial processes. A profound knowledge about influences of different parameters on the solid distribution in the material is required for an effective targeted impregnation process. Experimental investigations and simulations are used to study the influence of pore structure, drying conditions, and solute concentration on the solid distribution in porous support materials after impregnation and drying. It is found that low drying rates lead to strong solid accumulation at the material surface, whereas high drying rates reduce the solute transport to the surface and result in more uniform solid distributions. A small pore diameter and distribution width reduce solute migration during drying and lead to uniform solid distributions without being influenced by the drying conditions. A higher initial concentration of the impregnation solution causes pronounced surface accumulation, while low initial solute concentrations result in more uniform distributions. Fundamental effects during drying are captured in an existing pore network model by adaption of experimental pore structures and impregnation–drying conditions, resulting in a good general agreement of experiments with simulations.